IMPLEMENTASI PERATURAN DAERAH KABUPATEN SUKOHARJO NOMOR 6 TAHUN 2006 TENTANG PEMBENTUKAN BADAN PERMUSYAWARATAN DESA (BPD) DI DESA GROGOL KECAMATAN GROGOL KABUPATEN SUKOHARJO - Mursyd - - (JI@P, 2014)
The objective of the study is to describe the implementation of the establishmentof the Village Consultative Council (Badan Permusyawaratan Desa/BPD.Research was conducted in Grogol Village, Grogol Sub-districk, SukoharjoRegency. In this study the Van Meter and Van Horn Donals’ theory isexercised. Persons selected as samples were Grogol Head Village, FormationCommittee Members, BPD Establishment of Supervisory Teammembers, Member of BPD in Grogol Village, and communityleaders. Qualitative research strategy was used as the approach of the study.Research result showed that the findings are consistent with the theory putforward by Van Meter and Van Horn Donals. Implementation of establishmentof the BPD was effective, in accord to Act No. 6 of 2006 on the VillageConsultative Council. Factors affecting the implementation of BPD among othersare misinterpretation among the committee members concerning theimplementation of the formation of BPD; some members were apathic andindifference.Keywords: Village Consultative Council, Committee Member, BPD Establishmentof Supervisory Team